2021
DOI: 10.3390/cells10040798
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 in the Physiology and Pathology of the Central and Peripheral Nervous System

Abstract: S100A4 is a member of the large family of S100 proteins, exerting a broad range of intracellular and extracellular functions that vary upon different cellular contexts. While S100A4 has long been implicated mainly in tumorigenesis and metastatization, mounting evidence shows that S100A4 is a key player in promoting pro-inflammatory phenotypes and organ pro-fibrotic pathways in the liver, kidney, lung, heart, tendons, and synovial tissues. Regarding the nervous system, there is still limited information concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…There was no significant cell death was observed regardless the treatments applied ( Figure S3 A). It has been showed that inflammation have an effect on neuron differentiation 39 , 40 . Next, we sought to determine the neuronal differentiation in these cells treated with brain metabolites from GaELNs or PBS treated HFD mice.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant cell death was observed regardless the treatments applied ( Figure S3 A). It has been showed that inflammation have an effect on neuron differentiation 39 , 40 . Next, we sought to determine the neuronal differentiation in these cells treated with brain metabolites from GaELNs or PBS treated HFD mice.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TMEM16F inhibitor niclosamide and its analogs nitazoxanide, hexachlorophene and dichlorophen, present with intriguing anthelmintic, anticancer, and anti-ALS properties, indicating similar pathogenesis ( Peng et al., 2021 ). Indeed, as these agents target S100A4, a protein involved in schizophrenia and inhibited by the phenothiazine class of antipsychotic drugs, a common pathogenetic mechanism is being highlighted ( Malashkevich et al., 2010 ; D’Ambrosi et al., 2021 ). In addition, since S100A4 has also been implicated in tumorigenesis, it may be the common denominator between viral illness, cancer, and neuropsychiatric disorders ( Fei et al., 2017 ).…”
Section: Treatment Strategies For Pathological Cell-cell Fusionmentioning
confidence: 99%
“…S100A4 controls different cellular pathways, exerting numerous effects on processes that are cell- and tissue-type dependent. In activated fibroblasts, endothelial, dendritic, and mast cells, as well as in macrophages, monocytes, neutrophils, and T-lymphocytes, S100A4 has a significant role in stimulating invasion and migration, cytoskeletal dynamics and in promoting proinflammatory phenotypes [ 14 ]. S100A4 represents a well-known marker that characterizes a complex biological process where endothelial cells assume a mesenchymal phenotype, known as the “endothelial-to mesenchymal transition”, changing morphology and functions, acquiring accentuated motility and contractile properties, typical of fibrotic processes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%